Effect Of Extrusion Conditions On Physicochemical Properties Of Snacks From Commonly Grown Rice Varieties Of Kashmir (Applied Biological Research, 2016)
Five varieties of rice viz., ‘Shalimar Rice-I’, ‘Jhelum’, ‘K-332’, ‘China-1039’  and ‘Pusa Sugandh’, commonly grown in Kashmirvalley were assessed for  their extrusion behaviour. The rice obtained from above varieties was  ground to flour and subjected to extrusion processing. The experiment was  laid down in factorial completely randomized design with 3 feed moisture  levels (14, 6 and 18%) and 3 barrel temperature levels (120, 140 and 160oC).  The screw speed of 500 rpm was kept constant throughout the experiment.  The effects of feed moisture and barrel temperature on system parameters  (specific mechanical energy) product characteristics (density, expansion,  water absorption index (WAI), water solubility index (WSI), texture  (hardness) and colour of expanded rice snacks were studied. The study  revealed that bulk density, WAI, L* value (whiteness) and hardness of  snacks showed increase with increase in moisture content and decrease with  increase in barrel temperature. Volume expansion ratio, WSI and a*  (redness) and b* (yellowness) values showed decrease with increase in  moisture and increase with rise in barrel temperature. The ogranoleptic evaluation revealed 14% moisture content and 160oC barrel temperature as  most appropriate conditions for development of extruded snacks,  irrespective of the variety used. Further, based on the physico-chemical and  sensory attributes rice varieties ‘Shalimar Rice 1’ and ‘Jhelum’ were most  suitable for development of snacks using extrusion technology.
Keywords: Extrusion; feed moisture content; barrel temperature; rice; snacks